SAÚDE DA FAMÍLIA: IMPACTO NOS INDICADORES DE SAÚDE E NO MODELO DE ATENÇÃO? UMA ANÁLISE PRELIMINAR - KOPF, ÁGUIDA W.; FRANZ, LÍGIA B. B.; BURNELLO, MARISTELA B.; SILVA, MURIEL B. D.; GALVÃO, PEDRO L. D. S.; RIBEIRO, DANILO B.; HASS, CLARICE B. (Salão do Conhecimento, 2013)
Resumo